PENGARUH PENGGUNAAN MODEL PEMBELAJARAN COOPERATIVE LEARNINGTIPE THINK- PAIR- SHARE TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA SEKOLAH DASAR KELAS V - Gleni Mentari Purba (Jurnal Penelitian Pendidikan Indonesia (JPPI), 2025)
This abstract briefly presents the problem, objectives, methods, results, and conclusions of a study This abstract briefly presents the problem, objectives, methods, results, and conclusions of a study on the effect of the Cooperative Learning model, specifically the Think-Pair-Share technique, on the reading comprehension abilities of fifth-grade elementary school students. This research is motivated by the increasingly complex reading challenges in the information age, where many students struggle to understand texts, impacting their ability to grasp ideas and think critically. Factors such as ineffective teaching methods, lack of interest in reading, and limited access to quality reading materials exacerbate this issue. The objectives of this study are to measure the extent to which the Think-Pair-Share cooperative learning model can enhance students' reading comprehension abilities, to determine the difference in reading comprehension abilities between students who use the cooperative learning model and those who do not, and to understand students' responses to the implementation of this learning model. The method used is quantitative research with a pre-test, post-test, and evaluation sheet design targeting the population of fifth-grade students at SDN Baros Mandiri. The sample was drawn from all students in class 5A. The results indicate an improvement in students' reading comprehension abilities after the implementation of this learning model, suggesting the effectiveness of the Cooperative Learning model in reading instruction.